Fundamentals of ornamental fish health - Roberts, Helen E. [ (Helen Elizabeth)] , 1964- (Wiley-Blackwell, 2010)
This book is a complete guide to managing the health and well-being of ornamental aquatic animals. Grounded in the foundations of fish medical care, the book summarizes nonlethal aquatic diagnostics and medicine, putting the information within a clinical context. Providing a comprehensive overview of the subject, Fundamentals of Ornamental Fish Health equips aquatic animal health professionals with all the information needed to competently and effectively treat these patients, from transporting and examining fish to diagnostic techniques and the identification